Effect of Dietary N-3 Series Fatty Acids on Sperm Motility Duration of Rainbow Trout (Oncorhynchus Mykiss Walbaum, 1792) - Kaya, Seyma Ozer; Gur, Seyfettin; Koprucu, Kenan; Turk, Gaffari; Sonmez, Mustafa; Ozcan, Sinan (Marmara Univ, Inst Health Sciences, 2020)
Objective: This study was performed to determine the effect of different ratios of n-3 series fatty acids added to the diets of rainbow trout (Oncorhynchus mykiss) on sperm motility duration. Methods: A total of 48 male rainbow trouts about 3 years of age were used in the study and 4 groups were formed. The one that n-3 series fatty acids were not added to the diet was used as control group. n-3 series fatty acids were added to the experimental groups diets at the ratios of 1% (E1), 2% (E2) and 3% (E3), respectively. Semen was collected by abdominal massage. The time-dependent sperm motility change was detected under the microscope at x400 magnification. Results: A significant decrease was detected in the motility only at 360th hour in E3 group compared to the control group (p<0.05). Conclusion: As a result, it was concluded that feeding with diets containing different ratios of n-3 series fatty acids had no effect on the motility of rainbow trout semen under in vitro condition.
Keywords: Diet; duration of motility; fatty acid; rainbow trout; sperm motility